The Implementation of Reading Assessment Method - Dhion Meitreya Vidhiasi (ITScience (Information Technology and Science), 2022)
English, which is still considered a foreign language in Indonesia, has an impact on the teaching and learning process that is not optimal. This refers to the low proficiency in English, especially those of the Akademi Maritim Nusantara (AMN) Cilacap students. Good reading skills are one of the skills that AMN Cilacap students must possess. This is in line with the mission of the Ministry of Education and Culture of the Republic of Indonesia which makes reading and writing literacy the first position of the 6 (six) literacy abilities that must be possessed. The measurement of reading ability can be done in various ways. This study aims to see what methods are used by English language lecturers in assessing the reading ability of AMN Cilacap students. Also, the researcher wanted to see what methods the lecturer used most often. Researchers conducted a small survey of 2 (two) lecturers who taught English courses from 2 (two) different study programs, namely Marine Engineering and Port Management. Researchers distributed 2 (two) kinds of questionnaires which were then supported by interviews with each lecturer. The results show that there are 6 (six) methods used by the two lecturers in assessing reading skills. The Perceptive Task method is the method most often used. Even so, in choosing the right assessment method, the lecturer must also understand the conditions and level of understanding possessed by students.